2002
DOI: 10.1124/jpet.102.038331
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Profile of the Novel Inotropic Agent (E,Z)-3-((2-Aminoethoxy)imino)androstane-6,17-dione Hydrochloride (PST2744)

Abstract: The novel Na ϩ /K ϩ -ATPase inhibitor (E,Z)-3-((2-aminoethoxy)-imino)androstane-6,17-dione hydrochloride (PST2744) was characterized for its inotropic and toxic properties. Inhibition potency on dog kidney Na ϩ /K ϩ -ATPase was comparable (0.43 M) to that of digoxin (0.45 M). PST2744 concentration-dependently increased force of contraction in guinea pig atria and twitch amplitude in isolated guinea pig myocytes; in the latter, aftercontractions developed significantly less than with digoxin. Intravenous infusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 23 publications
1
45
0
2
Order By: Relevance
“…Istaroxime represents a new class of Na + /K + -ATPase inhibitors and stimulates SERCA, thereby exhibiting inotropic and lusitropic effects [131,132]. In animal models, this new drug exerts inotropic activity comparable with that of digitalis but produces less arrhythmia [133]. Initial clinical trials demonstrated a good safety profile, though future studies are needed before the drug can be considered for clinical use.…”
Section: Novel Therapies For the Septic Heartmentioning
confidence: 99%
“…Istaroxime represents a new class of Na + /K + -ATPase inhibitors and stimulates SERCA, thereby exhibiting inotropic and lusitropic effects [131,132]. In animal models, this new drug exerts inotropic activity comparable with that of digitalis but produces less arrhythmia [133]. Initial clinical trials demonstrated a good safety profile, though future studies are needed before the drug can be considered for clinical use.…”
Section: Novel Therapies For the Septic Heartmentioning
confidence: 99%
“…Based on these reports, our group addressed previously the anti-cancer potential of various Na + /K + ATPase inhibitors [6, 7], showing strong activity in multiple cancer cell lines in vitro , as well as in prostate and lung cancer xenografts in vivo [8, 9]. Focusing on istaroxime we demonstrated in a more recent study strong anti-cancer activity of this compound acting through caspase-3, c-Myc, actin reorganization and RhoA signaling in various cancer cell lines in vitro , as well as in prostate cancer xenografts in vivo [10].…”
Section: Introductionmentioning
confidence: 99%
“…It has a proposed mechanism of action that involves inhibition of sodium-potassium adenosine triphosphatase (Na-K ATPase) activity at the sarcolemma leading to an increase in cytosolic calcium and stimulation of sarcoplasmic reticulum calcium ATPase isoform 2 (SERCA2), leading to its rapid sequestration back into the sarcoplasmic reticulum during diastole [70]. The impact of istaroxime on calcium cycling in the cardiomyocyte would be expected to have favorable effects on both inotropic and lusitropic properties in the failing heart.…”
Section: Istaroximementioning
confidence: 99%
“…The impact of istaroxime on calcium cycling in the cardiomyocyte would be expected to have favorable effects on both inotropic and lusitropic properties in the failing heart. In fact, in animal models, istaroxime has been reported to improve systolic and diastolic function without increasing myocardial oxygen consumption [70][71][72]. The dose dependent effects of istaroxime on LV ejection fraction in an animal model of heart failure are depicted in Figure 7.6.…”
Section: Istaroximementioning
confidence: 99%